UK reveals existence of its military cyber operations unit. Issue 12 (December 2020) - Unknown
Abstract : The UK Government has revealed the existence of a military cyber operations unit. The recently created National Cyber Force (NCF) will be operated as a partnership between the Ministry of Defence (MoD) and the GCHQ signals intelligence agency.